Probiotics as multifaceted oral vaccines against colon cancer: A review - Singh, Shubhi; Singh, Manisha; Gaur, Smriti (Frontiers in Immunology, 2022)
Probiotics are known as the live microorganisms that, upon adequate administration, elicit a health beneficial response inside the host. The probiotics are known as immunomodulators and exhibit anti-tumor properties. Advanced research has explored the potential use of probiotics as the oral vaccines without the latent risks of pathogenicity. Probiotic-based oral vaccines are known to induce mucosal immunity that prevents the host from several enteric infections. Probiotic bacteria have the ability to produce metabolites in the form of anti-inflammatory cytokines, which play an important role in the prevention of carcinogenesis and in the activation of the phagocytes that eliminate the preliminary stage cancer cells. This review discusses the advantages and disadvantages of using the oral probiotic vaccines as well as the mechanism of action of probiotics in colon cancer therapy. This review also employs the use of “PROBIO” database for selecting certain probiotics with immunomodulatory properties. Furthermore, the use of several probiotic bacteria as anti-colon cancer adjuvants has also been discussed in detail. Because the current studies and trials are more focused on using the attenuated pathogens instead of using the probiotic-based vaccines, future studies must involve the advanced research in exploiting the potential of several probiotic strains as adjuvants in cancer therapies.